Enhancing the Quality of Education through Effective Governance in Higher Education - Bannaga Taha Hussen; Saifaldin Idris Onia (Nurul Jadid University, 2024)
This research focuses on applying governance principles in the faculties of education of Arab universities, highlighting three main elements: information disclosure, accountability in performance evaluation, and digitization of administrative data management. This research used a qualitative method with a case study. Data were collected through in-depth interviews, observation, and documentation, then analyzed using data reduction, display, and verification techniques. The results showed that information disclosure creates an inclusive and collaborative work environment, increases trust, and encourages active participation in decision-making. Accountability in performance evaluation is implemented through periodic reports that include achievements and recommendations for improvement, strengthening collective responsibility and transparency. Meanwhile, digitization of data management is still at an early stage, with barriers such as a lack of archiving standards and adequate technological infrastructure. Nonetheless, efforts to increase digitization are beginning to show positive results in administrative efficiency. This research significantly contributes to exploring the literature on higher education governance, particularly in the Arab region, by affirming the importance of integrating information disclosure, accountability, and digitization. The implication is that universities must adopt a holistic governance approach to improve management quality and global competitiveness. Further research is recommended to explore a broader context and test the generalizability of these findings.